A Measurement Framework for Analyze The Influence of Service Quality and Website Quality on User Satisfaction (Case Study: An IT Service in Jember University) - Beny Prasetyo; Fahrobby Adnan; Shinta Wardhani (IAES Indonesia Section, 2018)
The information system is a set tools to present information that has been managed well in order to make it easy and useful for its users. One indicator of the successful implementation of information system is how the end-user satisfaction. User satisfaction can be measured using user satisfaction methods. This study aims to develop a measurement framework to measure the user satisfaction of IT services. The measurement framework will be developed using 3 (three) basic theories such as Servqual by Parasuraman, Webqual by Barnes and Vidgen, and Information System Succes Model (ISSM) by DeLone and McLean. The model will be applied to a case study that an IT Service called Sistem Informasi Terintegrasi (SISTER) of the Jember University. This measurements using 100 respondents are students as SISTER's users and will be tested using t testing and GAP analysis. Based on the measurement results, the variable service quality has no significant influence on user satisfaction, and another variable is website quality has a significant influence on user satisfaction. Based on GAP analysis, it's found that the average gap value for service quality variable is -1.12, website quality is -1.00, and user satisfaction is -1.00. It means, the service quality that represents the tangible components, reliability, responsiveness, assurance, and emphaty of SISTER's provider according the students perceptions are still not good. In the future, SISTER's provider need to improve the quality of measurement items of indicators of reliability, responsiveness, assurance, and emphaty if they want to increase the user satisfaction of SISTER.